Study of cellulose acetate prepared from spinning combing waste: دراسة أسيتات السيللوز المحضر من عوادم تمشيط الغزل - Dema Esmail Shbib, Hussain Ahmad Bakr (Journal of engineering sciences and information technology, 2022)
Acetate Cellulose (CA) is a natural polymer from cellulose used mainly in the manufacture of filters, films, and plastics. Natural polymers have been mainly used in industrial and biological fields due to their safety and low production costs, and biodegradability. The study focuses on preparing acetate polymer from spinning waste by different methods with acetic acid 80% at acetylation time (15- 30) minutes and 70% acetic acid at a acetylation time (120- 180) minutes. (Experimental values were obtained based on the speed of forming a network of cellulose acetate fibers prepared on the electrospinning apparatus). The prepared (CA) was tested with a nuclear magnetic resonance (NMR) test, the thermal behavior was determined by the DSC test. The research shows that high (DS) was obtained at concentration 70% and high acetylation time, while the (DS) was lower at 80% concentration and low acetylation time. From the DSC test, we find that both the glass transition and melting temperature decrease with increasing the (DS), while the crystallinity increases with decreasing the (DS).